Impact of health education intervention on nutritional status among adolescent girls in government secondary schools Maiduguri: A randomised control trial - Shapu, Ruth Charles; Ismail, Suriani; Lim, Poh Ying; Ahmad, Norliza; Garba, Hussaini; Njodi, Ibrahim Abubakar (Bentham Science Publishers, 2023)
Background: The study aimed to evaluate the impact of a health education intervention on nutritional status among adolescent girls in government secondary schools in Maiduguri Metropolitan Council. Methods: The study was a randomized control trial among 417 adolescent girls aged 10-19 years old. Data were collected from October 2019 to March 2020 using KoBo collect toolbox. Chi-square and Fisher exact were used to compare baseline differences between the intervention and control group, a generalized estimating equation was used to evaluate the impact of health education intervention. Results: There was no significant difference in nutritional status (body mass index for age percentile and mid-upper arm circumference) between the intervention and control group at baseline. There was a statistically significant difference at three and six-months post-intervention for body mass index for age percentile p = 0.005; p < 0.001, while the mid-upper arm circumference was statistically significant at three months post-intervention p < 0.001, but not statistically significant at six months post-intervention. Conclusion: It is clear that health education intervention has an important role in improving the nutritional status of adolescents.